Pengaruh Model Pembelajaran Kooperatif Tipe Think Pair Share Dan Gaya Kognitif Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Biologi Kelas XI IPA MAN 2 Model Palu - Nurhaeda Nurhaeda; A. Tanra Tellu; Achmad Ramadhan (Universitas Tadulako, 2016)
This study aimed to: (1) describe the influence of cooperative learning model of TPS type and cognitive style toward the students’ learning result on Biology subject of the XI grade Science Program at MAN 2 Model Palu. This study applied quasi experimental method. The population of this study engaged 108 students which were administered into four classes. The sample for this study were selected through the implementation of random sampling technique, thus there were two classes selected with 48 students involved. The data collected in this study was the post-test scores which were analyzed through inferential statistic method. The data analysis drew on two-way Annova. The result of the analysis showed that: (1) The cooperative learning model of TPS type has contributed a significant effect toward students’ learning achievement. This model has surpassed the Direct Instruction model, (2) Cognitive style has significantly influenced toward students’ learning achievement. Students with field independent cognitive style have a higher learning achievement rather than those who were with field dependent cognitive style, (3) the interaction between learning model and cognitive style has no significant effect on students’ learning achievement. This has proved that learning model and cognitive style has functioned independently.